Simultaneous opto-acoustic light storage at multiple frequency channels - Stiller, Birgit; Merklein, Moritz; Vu, Khu; Ma, Pan; Madden, Stephen J.; Eggleton, Benjamin J. (2017 Conference on Lasers and Electro-Optics Pacific Rim, CLEO-PR 2017, 2017)
We store optical data in acoustic waves on a planar waveguide based on stimulated Brillouin scattering (SBS) and demonstrate for the first time that this coherent light storage concept allows for the simultaneous storage at different frequency channels, separated by 100 GHz, without observable cross-talk between the individual channels.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Nonlinear optics; Photonic integrated circuits; Stimulated Brillouin scattering